The Association Between Family Support and Coping Mechanisms Among People Living with HIV at Pesantren Community Health Center I, Kediri City - Byba Melda Suhita; Aprillia Nuril Hidayanti (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2026)
HIV/AIDS remains a serious problem in Indonesia, with cases increasing year after year. People living with HIV/AIDS (PLHIV) are potentially exposed to high levels of stress, so they must have family support and effective coping mechanisms. This study aims to determine the effect of family support on coping mechanisms among PLHIV at the Pesantren I Community Health Center in Kediri City. This study used an observational analytical design with a cross-sectional approach. A simple random sampling technique was used to obtain a sample of 200 respondents. The study consisted of two variables the independent variable of family support and the dependent variable of coping mechanisms of PLHIV. The research instrument used in this study was a questionnaire. The statistical test used was Spearman's Rho to determine the influence between variables. The study found that 94 respondents (47%) had high levels of family support and 129 respondents (65%) had good coping mechanisms. The analysis showed no significant effect between family support and coping mechanisms of PLHIV at the Pesantren I Community Health Center in Kediri City, with a p-value of 0.481 > 0.05. Coping mechanisms can be influenced by various factors, not just family support. Further research is needed to demonstrate this using the same subjects but different variables, so that new findings can be obtained.